RETRACTED ARTICLE: PIWIL2 restrains the progression of thyroid cancer via interaction with miR-146a-3p - Xiaoxiao Lu; Qingyun Zhu; Hong Du; Mingjun Gu; Xiangqi Li (BMC Endocrine Disorders)
Abstract Objective The classical role of PIWIL2 is to regulate reproduction by binding to piRNA, but its tumor-related function has received increasing attention in recent years. This study aims to explore its role in the progression of thyroid cancer (TC). Methods First, we measured and analyzed the levels of PIWIL2 and miR-146a-3p in TC tissue and adjacent tissues as well as several TC cell lines. We demonstrated the clinical significance of PIWIL2 and miR-146a-3p through the survival rate. Based on these results, we selected TPC-1 and KTC-3 cell lines for our cell experiments. We treated these cell lines with PIWIL2 lentivirus, PIWIL2 siRNA, miR-146a-3p mimic, or miR-146a-3p inhibitor and measured cell proliferation, cell cycle, apoptosis, migration, and invasion. We used PCR and Western blot to quantify the mRNA and protein levels of PIWIL2, while we used luciferase reporter assay and RNA binding protein immunoprecipitation to explore the relationship between miR-146a-3p and PIWIL2. Finally, we developed a xenograft tumor model to confirm the effects of the miR-146a-3p/PIWIL2 axis on TC progression in vivo. Results We identified that PIWIL2 and miR-146a-3p exhibit opposite expression alterations in TC tissues and that PIWIL2 serves as a ‘sponge’ by adsorbing miR-146a-3p. Up-regulating PIWIL2 decelerated the proliferation, metastasis, and cell cycle progression of TPC-1 and KTC-3 cells, but accelerated the apoptosis of TC cells, while miR-146a-3p exhibited opposite effects. Finally, overexpressing PIWIL2 restrained the progression of TC in nude mice, which can be reversed by increasing miR-146a-3p expression. Inhibiting PIWIL2, on the other hand, promoted the progression of TC in vivo, which can be reversed by inhibiting miR-146a-3p. Conclusion PIWIL2 may inhibit the progression of TC by sponging miR-146a-3p, providing new insights into the early treatment, recrudescence treatment, and metastasis treatment of TC.